2018
DOI: 10.18805/ijar.b-1006
|View full text |Cite
|
Sign up to set email alerts
|

Effects of dietary supplement of mulberry leaf (Morus alba) on growth and meat quality in rabbits

Abstract: This research evaluated the effects of mulberry leaf in diet on growth and meat quality in rabbits. Five treatment diets were prepared by using a proportion of 0% (CK), 5% (ML5), 10% (ML10), 15% (ML15) and 20% (ML20) mulberry leaf powder (MLP), respectively. Results showed that average daily gain (ADG) in the ML20 group was significantly (P£ 0.05) lower than that in the CK, ML5 and ML10 treatments. Feed conversion ratio (FCR) in the ML20 treatment was significantly (P£ 0.05) higher than… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
3
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 16 publications
1
3
0
Order By: Relevance
“…Similar results were also observed in a study investigating the effects of MLM supplementation on poultry meat quality (Ding et al, 2021). Similar results were observed in pigs (Liu et al, 2019;Zeng et al, 2019) and rabbits (Wu et al, 2019;Hou et al, 2020) with the addition of MLM. However, the mechanism underlying how mulberry leaf changed the muscle fibre types is unclear.…”
Section: Resultssupporting
confidence: 86%
“…Similar results were also observed in a study investigating the effects of MLM supplementation on poultry meat quality (Ding et al, 2021). Similar results were observed in pigs (Liu et al, 2019;Zeng et al, 2019) and rabbits (Wu et al, 2019;Hou et al, 2020) with the addition of MLM. However, the mechanism underlying how mulberry leaf changed the muscle fibre types is unclear.…”
Section: Resultssupporting
confidence: 86%
“…Previous studies have shown that mulberry leaves affect feed intake and intestinal development in animals, prolong the retention of chyme in the intestinal tract, and increase intestinal weight ( Prasad et al., 2003 ; Simol et al., 2012 ; Hou et al., 2020b ). In our study, DNJ did not greatly affect feed intake, neither did it affected intestinal development or cause chyme accumulation.…”
Section: Discussionmentioning
confidence: 99%
“…The content of crude protein and carbohydrate in mulberry leaves is significantly higher than those in other green forage and is comparable to that of high-quality legume forage such as alfalfa ( Doran et al., 2007 ). At present, as a feed or feed additive, mulberry leaf has been widely used in the breeding of ruminants, rabbits, and pigs and has been reported to significantly improve the yield and quality of meat and milk ( Chhay et al., 2010 ; Venkatesh Kumar et al., 2015 ; Ma et al., 2017 ; Hou et al., 2020b ).…”
Section: Introductionmentioning
confidence: 99%
“…For instance, although China is the world's largest mulberry grower, with an annual output of 20 tonnes per ha, its mulberry leaf utilization rate is only 1%-3% . It is mainly used as silkworm feed, while a small amount of mulberry leaf powder is directly added to the feed of domestic animals, such as broilers (Islam et al, 2014), beef cattle (Huyen et al, 2012), meat rabbits (Hou et al, 2020) and meat geese (Wang et al, 2017).…”
mentioning
confidence: 99%